The Effect of Buds Location on Stem Cuttings on Sugarcane (Saccharum officinarum L.) Germination - Mahrus Ali; Yeni Ika Pratiwi (Agro Bali : Agricultural Journal, 2022)
The purpose of the study was to determine the extent of the effect of using planting material (seeds with buds on different segments of one stem on germination in an effort to improve the quality of sugarcane cultivation techniques. This research method used a Randomized Block Design (RBD) experiment with three replications. The detail treatment was as follows: M1: budding eyes number 7b M2: budding eyes number 8, M3: budding eyes number 9 M4: budding eyes number 10, M5: budding eyes number 11, M6: budding eyes number 12, M7: budding eyes number 13, M8: budding eyes number 14, M9: budding eyes number 15. Using the Excel data analysis tool, the results showed a very significant effect on the acceleration of germination and dry weight of sprouts, as well as a significant effect on the number of leaves, number of roots, length roots, and increased wet weight due to the treatment of the location of the buds on the stem cuttings of sugarcane plants acceleration of germination and root length as well as wet weight and dry weight to The best sprouts were indicated by the treatment of the location of the 11th segment (M5) buds. The highest number of leaves and number of roots was indicated by the location of the buds 12 (M6). The acceleration of increasing the number of leaves, number of roots, root length, wet weight and dry weight of the lowest sprouts is always indicated by the location of the shoots on Section 7 (M1).